Meta Salud Diabetes for cardiovascular disease prevention in Mexico: a cluster-randomized behavioural clinical trial. (11th April 2021) - Rosales, Cecilia B; Denman, Catalina A; Bell, Melanie L; Cornejo, Elsa; Ingram, Maia; del Carmen Castro Vásquez, María; Gonzalez-Fagoaga, Jesús Eduardo; Aceves, Benjamín; Nuño, Tomas; Anderson, Elizabeth J; Guernsey de Zapien, Jill
Abstract: Background: Healthy lifestyle interventions offered at points of care, including support groups, may improve chronic disease management, especially in low-resource populations. We assessed the effectiveness of an educational intervention in type 2 diabetes (T2D) support groups to reduce cardiovascular disease (CVD) risk. Methods: We recruited 518 participants to a parallel, two-arm, cluster-randomized, behavioural clinical trial across 22 clinics in Sonora, Mexico, between August 2016 and October 2018. We delivered a 13-week secondary prevention intervention, Meta Salud Diabetes (MSD), within the structure of a support group (GAM: Grupo de Ayuda Mutua ) in government-run (community) Health Centres ( Centros de Salud ). The primary study outcomes were difference in Framingham CVD risk scores and hypertension between intervention (GAM+MSD) and control (GAM usual care) arms at 3 and 12 months. Results: CVD risk was 3.17% age-points lower in the MSD arm versus control at 3 months [95% confidence interval (CI): −5.60, −0.75, P = 0.013); at 12 months the difference was 2.13% age-points (95% CI: −4.60, 0.34, P = 0.088). There was no evidence of a difference in hypertension rates between arms. Diabetes distress was also lower at 3 and 12 months in the MSD arm. Post-hoc analyses showed greater CVD risk reduction among men than women and among participants with HbA1c < 8. Conclusions: MSD contributed to a positive trend in reducing CVD risk in a low-resource setting. This study introduced an evidence-based curriculum that provides T2D self-management strategies for those with controlled T2D (i.e. HbA1c < 8.0) and may improve quality of life.